Application of Demonstration Method in Learning Maharah Kalam in the Darussalam School Lawang Malang: Penerapan Metode Demonstrasi Dalam Pembelajaran Maharah Kalam di Sekolah SMA Darussalam Lawang Malang - Roziqin, Akhmad Zainur; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the application of the Demonstration Method in improving Maharah Kalam (speaking skills) among students at Darussalam School in Lawang Malang. The traditional approach to teaching Maharah Kalam often lacks variation, resulting in limited student understanding and confidence in speaking Arabic. To address this issue, a new program, the Demonstration Method, was implemented. A qualitative research methodology was employed, utilizing participatory observation techniques, interviews, and document studies for data collection. Data analysis involved techniques such as data reduction, presentation, and drawing conclusions. The findings revealed that the implementation of the Demonstration Method through the Arabic Club Program, consisting of Arabic dialogue, Arabic games, and Arabic activities, significantly enhanced students' Maharah Kalam skills. This study provides valuable insights for educators seeking effective strategies to promote language learning and highlights the implications of the Demonstration Method for fostering linguistic competence in Arabic-speaking contexts. Highlights: The Demonstration Method: An innovative approach for improving Maharah Kalam skills. Enhancing language learning: The impact of the Demonstration Method in fostering Arabic proficiency. Educational implications: Promoting effective language instruction through interactive and varied learning activities. Keywords: Demonstration Method, Maharah Kalam, Language Learning, Arabic Skills, Educational Innovation